The Effect of Compensation on Employee Performance At Pt Charoen Pokphand Jaya Farm Unit 3 Sumedang - Hidayat, Gustina; Dewi, Khisti Hanila; Mubarokah, Robbani Hablie (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
Employee management is very important for the sustainability of the company because employees are the tip of the iceberg of the company's strategy achievement. One of the company's strategies in managing employees by providing compensation is given. Compensation makes employees highly motivated to produce good performance. PT Charoen Pokphand Jaya Farm Unit 3 Sumedang once provided salaries below the minimum wage of Sumedang Regency and there was a decrease in incentives from 2023 to 2024, the method used was quantitative, by disseminating data to 32 employees. Based on the results of the analysis, it is known that the overall score of the compensation statement is 2,056 and the overall score of the employee performance statement is 2,300 in the good category. The results of the simple linear regression analysis test obtained a linear regression equation model Y = 33.922 + 0.591X and a significance value of 0.012 is less than 0.05, and based on the results of the t-test, the calculated t-value of 2.666 is greater than the t-table of 2.042, so that the H0 hypothesis is rejected meaning that compensation has an effect on employee performance